2000
DOI: 10.1508/cytologia.65.129
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic Effects of Gamma Rays and Ethyl Methane Sulphonate in Chilli Pepper (Capsicum annuum L.).

Abstract: Summary Seeds of Capsicum annuum L. var. G-4 Bhagyalakshmi were subjected to 15, 25, 35 kR doses of gamma ray, and 0.8% and 1% ethyl methane sulphonate (EMS). Effects of mutagenic treatments of meiosis viz. chromosomal anamolies, pollen sterility, seed sterility and survival percentage in M2 generation have been reported. EMS was found more effective in inducing meiotic irregularities than gamma ray treatment. A dose dependent increase in meiotic anomalies was obtained with all the mutagenic treatments.Mutatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 5 publications
7
8
0
Order By: Relevance
“…The percentage of meiotic abnormalities was higher under EMS than in the SA and gamma ray treatments. Different types of chromosomal abnormalities observed in the present study have been reported for other plant systems after treatment with physical and chemical mutagens (Kumar & Dubey 1998;Dhanayanth & Reddy 2000;Bhat et al 2005).…”
Section: Meiotic Analysissupporting
confidence: 74%
“…The percentage of meiotic abnormalities was higher under EMS than in the SA and gamma ray treatments. Different types of chromosomal abnormalities observed in the present study have been reported for other plant systems after treatment with physical and chemical mutagens (Kumar & Dubey 1998;Dhanayanth & Reddy 2000;Bhat et al 2005).…”
Section: Meiotic Analysissupporting
confidence: 74%
“…The induced chromosomal variations have been extensively investigated from the point of view of understanding the damaging effects of the mutagen on the concerned plant. Different types of chromosomal aberrations as noticed in the present study have also been reported earlier by many workers in different plants after physical or chemical mutagenic treatments (Ahmad and Godward 1981;Dhamyanthi and Reddy 2000;Kumar and Singh 2003;Basi et al 2006;Khan et al 2009;Das et al 2010;Chatterjee et al 2011). Dose dependent increase in the chromosomal abnormalities was also reported by Singh and Chaudhary (2005) in Capsicum annuum L., Basi et al (2006) in Indica rice, Radha-4, Khan et al (2009) and Sharma et al (2009) in Vicia faba L. and Chatterjee et al (2011) in Papaver somniferum L. Induction of cytological disturbances in the mitotic as well as meiotic cells is of great value, as it results in the genetic damage that is handed over to the next generation (Kumar and Rai 2007).…”
Section: Resultssupporting
confidence: 90%
“…The mutagenic effect of EMS could be related to its ability to induce nuclear alterations in the form of nuclear buds, micronuclei, irregular nuclei, etc., as well as various types of chromosomal aberrations such as stickiness, precocious movement of chromosomes, unorientation, univalents and multivalent at metaphase I/II, and laggards and bridges at anaphase I/II in the pollen mother cells of Phaseolus vulgaris L. There has been a significant enhancement in chromosomal anomalies along with increasing concentrations of EMS. Similar results have been obtained by other workers in different plants with different chemical and physical mutagens (Ahmad 1993, Dhamayanthi and Reddy 2000, Bhat et al 2005, Kumar and Rai 2007.…”
Section: Discussionsupporting
confidence: 89%